Difference between “Lung Age” and Real Age as a Novel Predictor of Postoperative Complications, Long-Term Survival for Patients with Esophageal Cancer after Minimally Invasive Esophagectomy - Hong, Zhi-Nuan; Weng, Kai; Chen, Zhen; Peng, Kaiming; Kang, Mingqiang (Frontiers in Surgery, 2022)
Background This study aimed to investigate whether the difference between “lung age” and real age (L–R) could be useful for the prediction of postoperative complications and long-term survival in patients with esophageal cancer followed by minimally invasive esophagectomy (MIE). Methods This retrospective cohort study included 625 consecutive patients who had undergone MIE. “Lung age” was determined by the calculation method proposed by the Japanese Respiratory Society. According to L–R, patients were classified into three groups: group A: L–R ≦ 0 (n = 104), group B: 15 > L–R > 0 (n = 199), group C: L–R ≥ 15 (n = 322). Clinicopathological factors, postoperative complications evaluated by comprehensive complications index (CCI), and overall survival were compared between the groups. A CCI value >30 indicated a severe postoperative complication. Results Male, smoking status, smoking index, chronic obstructive pulmonary disease, American Society of Anesthesiologists status, lung age, and forced expiratory volume in 1 s were associated with group classification. CCI values, postoperative hospital stays, and hospital costs were significantly different among groups. Multivariate analysis indicated that L–R, coronary heart disease, and 3-field lymphadenectomy were significant factors for predicting CCI value >30. Regarding the prediction of CCI value >30, area under the curve value was 0.61(95%: 0.56–0.67), 0.46 (95% CI, 0.40–0.54), and 0.46 (95% CI, 0.40–0.54) for L–R, Fev1, and Fev1%, respectively. Regarding overall survival, there was a significant difference between group A and group B + C (log-rank test: p = 0.03). Conclusions Esophageal cancer patients with impaired pulmonary function had a higher risk of severe postoperative complications and poorer prognosis than those with normal pulmonary function. The difference between “lung age” and “real age” seems to be a novel and potential predictor of severe postoperative complications and long-term survival.